The Moderating Impact of Dividend Policy and Corporate Social Responsibility On Profitability towards Firm Value - Widya Sari; Leo Indra Pratama; David Fu; Claudie Lim (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
This research targets are to identify and analyze not only the influence of profitability towards firm value but also the ability of both dividend policy and corporate social responsibility disclosure to moderate them on companies which are listed in the consumer goods industry on Indonesian stock exchange (IDX) from 2013 to 2017. There are precisely 39 and 14 enterprises that are utilized as population and sample respectively. This study applies the purposive sampling method to generate samples from the population which had been eliminated by the devoted criteria. Data has been analyzed by using multiple regression and moderation regression analysis. The result delineates that partially, profitability and dividend policy have a significant effect on firm value, while corporate social responsibility does not affect firm value. Simultaneously, the independent variables significantly affect the dependent variable.